'A divine attraction between your soul and mine': George Whitefield and same-sex affection in 18th-century Methodism. (June 2017) - O'Brien, Glen
This article considers the blurred lines between male friendship and homoeroticism in 18th-century Methodism. It considers possible cases of transgressive male sexual acts among Methodist preachers, evaluates contemporary claims made about the sexual proclivities of leading Methodists, and considers the social location of 18th-century Methodism as a dangerous underworld of deviant religiosity whose centres of activity were often perched on the edge of sites of social exclusion. The 'effeminacy' of George Whitefield and the lack of heterosexual passion in his life are offered as a mode of examining the homosociality that existed within the heteronormative world of 18th-century Methodism.